(untitled) (Research, Society and Development, 2022)
The effects of COVID-19 on children are still poorly understood. Considering the progressive increase in pediatric cases, we sought to gather evidence of the disease in children, to better understand its evolution, possible complications, and favor clinical practice. This is a review, whose search was carried out in the National Library of Medicine, Latin American & Caribbean Health Sciences Literature (LILACS), Medical Literature Analysis and Retrieval System Online, Virtual Health Library (BVS), PAHO and Cochrane Library. Eight articles were included, and the most common symptoms described were: cold-like symptoms, dry cough, respiratory difficulty, mild throat infection, loss of muscle strength, tonic and reflex changes in the lower limbs. However, there is still no clarity about the disease in children, requiring further research.